Analisis Perbandingan Komisi Yudisial Antara Negara Indonesia, Argentina, Meksiko dan Brazil - Shalsabila Putri Andon Pertiwi; Sunny Ummul Firdaus; Maria Madalina (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
This study aims to analyze the similarities and differences in the position and authority of the Judicial Commission in Indonesia, Argentina, Mexico and Brazil and analyze the challenges faced by the Indonesian Judicial Commission to optimize its duties and authorities. This study is a normative legal study with a comparative approach. The types of materials used are primary legal materials and secondary legal materials. The legal material collection technique used is document study or literature study. The data analysis technique uses the siligism method with a deductive thinking pattern. The results of the study are that the Judicial Commissions of Indonesia, Argentina, Mexico and Brazil have similarities related to the basic regulations regarding the Judicial Commission institution which are both regulated in the constitution and the composition of membership consisting of partisans. The differences between institutions similar to the Judicial Commission are related to authority, number of members and term of office. The challenges faced by the Judicial Commission are the limited authority held by the institution, and the overlapping authority between the Judicial Commission and the Supreme Court related to supervision.